Effect of Biofertilizers on Yield and Biomolecules of Anti-cancerous Vegetable Broccoli - Singh, A.; Maji, S.; Kumar, S. (International Journal of Bio-resource and Stress Management, 2023)
Broccoli is gaining its popularity as an important part of diet all over the world for its anti- oxidant and anti-cancerous properties. Present investigation was carried out to find out the effect of biofertilizersto improve yield and quality of broccoli. The biofertilizers viz. Azospirillum, PSB, Azotobacter and VAM were applied alone and in combinations,inorganic fertilizer as positive control and without manuring as negative control. It was observed that application of inoculants Azospirillum+Azotobacter (50% each) significantly increased the curd size (15.17 cm diameter) and curd yield (1.17 kg, 0.93 kg curd with and without guard leaves, respectively) of broccoli found maximum compared to other treatments. The results showed that Azospirillum (100%), PSB (100%) and Azotobacter (100%) also had better performance than the recommended dose of fertilizers, but other treatment combinations except Azospirillum+Azotobacter (50% each)performed poor than the recommended dose of fertilizer.Fourier Transform Infra-Red (FTIR) analysis was done to out find the significant presence of potential biomolecules in broccoli. Among the biofertilizer treatments use of Azospirillum+Azotobacter (50% each) clearly showed the improvement in protein and lipid profile along with phosphate and sulphate content of broccoli curd.Thus, the study concluded that use of Azospirillum+Azotobacter (50% each) was found better for improving the curd yield of broccoli and its active biomolecules.